(untitled) (World Bulletin of Social Sciences, 2024)
The article focuses on the forms of manifestation of cultural and spiritual and moral choice in the science and philosophy of modernity in harmony with the military sphere. In accordance with it, for a deeper study of the problem of spiritual choice, some methodological approaches to the problem of research, metaphysical, dialectical, existentialist, phenomenological, synergetic and postmodern approaches have been explored within the framework of the topic. In particular, the metaphysical approach focuses on the transcendental meanings of spiritual choice, indicating a priori motives for the implementation of alternatives.